Axillary intra-aortic balloon pump, biventricular assist device implantation and subsequent orthotopic heart transplantation in a patient with sickle cell trait. Issue 6 (18th June 2022) - Taylor, Marcus; Mouyer, Zakariya; Callan, Paul; Shaw, Steve; Venkateswaran, Rajamiyer; Nwaejike, Nnamdi
Abstract: A 38-year-old male with sickle cell trait and acute refractory heart failure received an axillary intra-aortic balloon pump and short-term biventricular assist device. He underwent orthotopic heart transplantation 45 days later, which was complicated by major bleeding necessitating significant intra-operative transfusion. Support with veno-arterial extracorporeal membrane oxygenation was provided and successfully weaned five days later. He made a full recovery and remains alive and well 34 months after discharge. We hypothesize that the protective peri-operative measures undertaken, including normothermia during surgery and post-operative haemodynamic stability due to the use of mechanical circulatory support, conveyed a degree of protection against complications associated with sickle cell dysfunction and contributed to the successful outcome.